Green Synthesis Of Titanium Dioxide Nanoparticles By Using Ethanolic Leaf Extract Of Jatropha Curcas L. - Madane, Kishor Dadaso; Kane, Sandeep Ravindra; Mohite, Shrinivas Krishna; Kamble, Shailaja Jaykumar; Deshmukh, Akshada Vivek; Shewale, Avani Krushnaji (Journal of Neonatal Surgery, 2025)
The current study presents a green, eco-friendly approach for the synthesis of titanium dioxide (TiO₂) nanoparticles using ethanolic leaf extract of Jatropha curcas L., a medicinal plant rich in bioactive compounds. Traditional chemical and physical synthesis methods often involve hazardous reagents and energy-intensive processes; in contrast, this biological method offers a sustainable alternative. The leaves were extracted via Soxhlet apparatus using ethanol as solvent, and the resulting extract was employed in the reduction and stabilization of TiO₂ nanoparticles. The synthesized nanoparticles were characterized using GC-MS, DLS, zeta potential, SEM, and XRD techniques. GC-MS analysis confirmed the presence of twelve major phytochemicals, such as (+)-2-Bornanone, caryophyllene, alpha-pinene, and flavonoids, which are known for their antioxidant and antimicrobial properties. DLS analysis revealed an average particle size of 125 nm with a PDI of 0.410, indicating moderate monodispersity. Zeta potential analysis showed a negative surface charge of -35.2 mV, confirming high colloidal stability. SEM images revealed rough, wrinkled surfaces suggesting high surface reactivity, while XRD analysis confirmed the crystalline anatase phase of TiO₂. Antioxidant activity assessed via DPPH assay demonstrated a significant dose-dependent response, with a maximum inhibition of 73.57% at 100 µg/mL and an IC₅₀ value of 75.08 µg/mL, comparable to ascorbic acid.